Review—Non-Invasive Monitoring of Human Health by Exhaled Breath Analysis: A Comprehensive Review. Issue 3 (3rd February 2020) - Das, Sagnik; Pal, Mrinal
Abstract : Exhaled human breath analysis is a very promising field of research work having great potential for diagnosis of diseases in non-invasive way. Breath analysis has attracted huge attention in the field of medical diagnosis and disease monitoring in the last two decades. VOCs/gases (Volatile Organic Compounds) in exhaled breath bear the finger-prints of metabolic and biophysical processes going on in human body. It's a non-invasive, fast, non-hazardous, cost effective, and point of care process for disease state monitoring and environmental exposure assessment in human beings. Some VOCs/gases in exhaled breath are bio-markers of different diseases and their presence in excess amount is indicative of un-healthiness. Breath analysis has the potential for early detection of diseases. However, it is still underused and commercial device is yet not available owing to multiferrious challenges. This review is intended to provide an overview of major biomarkers (VOCs/gases) present in exhaled breath, importance of their analysis towards disease monitoring, analytical techniques involved, promising materials for breath analysis etc. Finally, related challenges and limitations along with future scope will be touched upon.